2014
DOI: 10.1007/s10517-014-2368-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-1β on Peripheral Blood Leukocytes in Rats with Various Behavioral Characteristics during Acute Stress

Abstract: We studied the effect of a pro-inflammatory cytokine IL-1β (5 μg/kg intraperitoneally) on blood leukocytes in Wistar rats various behavioral characteristics during acute emotional stress (1-h immobilization with simultaneous delivery of subthreshold electrocutaneous stimulation). Stress exposure was accompanied by a decrease in the total number of peripheral blood leukocytes in rats. Active animals were characterized by the increase in neutrophil count during stress. The number of eosinophils in passive specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Several studies have reported that the percentage of peripheral monocytes was interictally elevated in patients with GLE/focal epilepsy [8,38]; moreover, the percentage seemed to be higher in patients with GLE than that was found in patients with focal epilepsy even after various types of antiepileptic medications [38].…”
Section: Count Change Of Peripheral Cells After Epileptic Seizurementioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have reported that the percentage of peripheral monocytes was interictally elevated in patients with GLE/focal epilepsy [8,38]; moreover, the percentage seemed to be higher in patients with GLE than that was found in patients with focal epilepsy even after various types of antiepileptic medications [38].…”
Section: Count Change Of Peripheral Cells After Epileptic Seizurementioning
confidence: 90%
“…PBCs express classical components of neurotransmitter systems [8], such as transporters of gamma-aminobutyric acid (GAT), serotonin (SERT), and receptors of glutamate (GluR), which mediate important communications between peripheral system and CNS. Recent studies have suggested that platelets participate in CNDs through multiple pathways, including interrupting the integrity of BBB [9], mediating the infiltration and clearance of neutrophils [10], regulating the uptake of serotonin [11], and gamma-aminobutyric acid (GABA) [12][13][14], or controlling the production of prostaglandin (PG) [15], and activation of phospholipase a2 (PLA2) [16], however, the mechanism underlying these signaling cascades still remains poorly investigated.…”
Section: Changes Of Pbcs After Epileptic Seizurementioning
confidence: 99%
See 1 more Smart Citation
“…Stress manifests itself as a systemic ramified reaction, accompanied by various impairments of physiological functions [9,12]. It is known that blood parameters are closely related to implementation of various physiological functions of the body [3]. Neutrophilia, lymphopenia, and eosinopenia are observed in the peripheral blood under conditions of negative emotiogenic loads [2].…”
mentioning
confidence: 99%
“…Neutrophilia, lymphopenia, and eosinopenia are observed in the peripheral blood under conditions of negative emotiogenic loads [2]. Calculation of the lymphocyte index (LI) of peripheral blood in animals, based on the analysis of the ratio of the number of lymphocytes to neutrophils, allows express-diagnostics of stress [3].…”
mentioning
confidence: 99%